Hitchcock on Hitchcock : selected writings and interviews - Hitchcock, Alfred, 1899-1980 (University of California Press, 1995)
Reputations come and go, but Alfred Hitchcock's has remained solidly in place in the pantheon of masters of the cinema. What is less known is that he wrote about the cinema during the course of his life, and his writings are presented here.
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Interviews.; Hitchcock, Alfred, -- 1899-1980; Motion pictures.; Motion pictures -- Production and direction.; Motion Pictures as Topic; Motion Pictures.; Cinéma -- Production et réalisation.; Cinéma.; PERFORMING ARTS -- Film & Video -- Direction & Production.; Interviews; Motion pictures; Motion pictures -- Production and direction; Films.